Vitamin D and cortisol as moderators of the relationship between testosterone and exercise performance in adolescent male athletes - Crewther, B.; Cook, C.; Fitzgerald, J.; Starczewski, M.; Gorski, M.; Orysiak, J. (Pediatric Exercise Science, 2020)
Reported associations between vitamin 25(OH)D and exercise performance are equivocal, perhaps due to complex interplay with cortisol and testosterone. In this study, the authors investigated serum 25(OH)D and cortisol as moderators of the testosterone relationship with exercise performance in adolescent male athletes. Methods: A total of 88 ice hockey players were assessed for serum 25(OH)D, cortisol, testosterone, body composition, and exercise performance, based on countermovement jump power and muscle torque. The authors tested independent relationships, before examining complex interactions via moderated regression analyses. Results: Most athletes (62.5%) exhibited a suboptimal (20-30 ng·mL-1) serum 25(OH)D concentration, whereas 9.1% of athletes were deficient (<20 ng·mL-1). Serum 25(OH)D was not related to performance when controlling for testing year, age, and fat mass. Further modeling revealed a significant hormonal interaction. Specifically, in low-25(OH)D subjects, testosterone predicted countermovement jump power at a high (ß = 7.10, effect size = .43, P < .01), but not low (ß = -3.32, effect size = -.20, P = .09), cortisol concentration. Conclusions: Serum 25(OH)D was a poor predictor of exercise performance, but it did moderate (with cortisol) the testosterone link to muscle power. Notably, this relationship emerged among individuals with a 25(OH)D concentration (~22 ng·mL-1) approaching the deficiency cutoff. Viewing 25(OH)D as a moderating, rather than dose responsive, variable could help explain equivocal cross-sectional associations.